Elements of Work Environment In The Construct Of Special Education Teacher Workload In Malaysia - et. al., Junaidah Yusof, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Work environment can be defined as an environmental condition within the scope of one’s task performance. For a teacher, the work environment is a situation in which the teachers perform their duties in a school organization. While for the scope of special education, the work environment is the state of work and the relationship between teachers, staff, students, administrators and parents. A harmonious and conducive work environment can help the execution of tasks in an orderly and perfect manner. A harmonious work environment is also able to build a good and excellent school. Therefore, this brief study was conducted to explore in more detail the elements of the work environment in providing a good commitment to the school. This qualitative study involved 11 coordinators in the state of Johor, Malaysia. It is hoped that these findings will be able to give a good impact to the next researcher in explaining about this issue.